The Effect of High-Intensity Intermittent Exercise with Silymarin Supplementation on Liver Enzymes in Male Rats of Fatty Liver Model - Minoo Dadban-Shahamat; Masoud Shakki; Seyedeh Zolaikha Hashemi-Chashmi (مجله دانشکده پزشکی اصفهان, 2021)
Background: Non-alcoholic fatty liver disease includes a spectrum of clinical syndromes from early steatosis to liver cirrhosis. Therefore, the aim of the present study was to investigate the effects of exercise training with silymarin supplementation on liver enzymes and weight of male fatty liver rats.